Friday, 15 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.5213
|View full text |Cite
|
Sign up to set email alerts
|

OP0244 An asas-positive mri of the sacroiliac joints can also occur in healthy individuals, runners and women with postpartum back pain

Abstract: BackgroundInflammation shown on MRI of the sacroiliac joint (MRI-SI) is prevalent in axSpA (±30%) but the specificity is not well known.ObjectivesTo compare MRI of the sacroiliac joints (MRI-SI) of healthy, symptomless individuals and those with known mechanical strain acting upon SI joints to axial spondyloarthritis (axSpA) and chronic back pain (CBP) patients.MethodsThree trained, calibrated and blinded readers randomly scored MRI-SI of 172 subjects: 47 healthy individuals without current/past back pain(;1 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…This finding is consistent with another study in healthy individuals, which found the same threshold of ≥5 SIJ quadrants with BME using the same MRI assessment module (31).…”
Section: Accepted Articlesupporting
confidence: 92%
“…This finding is consistent with another study in healthy individuals, which found the same threshold of ≥5 SIJ quadrants with BME using the same MRI assessment module (31).…”
Section: Accepted Articlesupporting
confidence: 92%
“…Regarding the axial skeleton including the spine and the sacroiliac joints (SIJs) this is particularly critical if identification of patients with axial spondyloarthritis (axSpA) is pursued. In this context our study1 confirms earlier data 2. We conclude that false positive MRI findings account for much of the confusion that has been created in relation to the Assessments in Spondyloarthritis International Society (ASAS) classification criteria 3…”
supporting
confidence: 87%
“…However, it is important to correctly interpret the MRI changes because it is known that at least some of the changes may also occur in healthy individuals. [2][3][4] "Reference biologics, such as anti-TNF therapy, have been shown to be effective in targeting inflammation, whether in the sacroiliac joints, the spine, or the peripheral joints such as the knee. Within 6-12 months, the inflammation is usually cleared, 5 but in up to 20% of cases, a follow-up MRI may reveal some residual inflammation.…”
Section: Identifying Patients Who Will Benefit Most From Biologic Tre...mentioning
confidence: 99%
“…Several studies [2][3][4] 1). 7 On that basis, therapy should be started as early as necessary to induce remission.…”
Section: Identifying Patients Who Will Benefit Most From Biologic Tre...mentioning
confidence: 99%